Factors Impacting the Use of an Allelochemical Lure in Pome Fruit for Cydia pomonella (L.) Monitoring - Alan Lee Knight; Michele Preti; Esteban Basoalto (Insects, 2025)
A four-component blend comprising pear ester, DMNT, linalool oxide, and acetic acid (CM4K) was identified as a potent allelochemical lure for both sexes of codling moth (CM), Cydia pomonella (L.). Studies conducted from 2020 to 2022 in Washington State (USA) examined factors which could impact the lure’s relative performance. The CM4K lure was effective across a range of mating disruption programs and was equally attractive in monitoring wild and sterile CM. The lure remained attractive for at least 10 weeks. Total catch in traps baited with the CM4K was significantly less impacted than a sex pheromone lure located near mating disruption dispensers and female catches were largely unaffected. Traps with the CM4K lure caught significantly more females and fewer males when placed near clusters of fruits in a trellised orchard. Two factors were found to significantly impact the relative performance of the CM4K to sex pheromone lures: the CM4K lure was only equivalent to sex pheromone lures in pear MD orchards, and apple and pear orchards with vigorous weed growth. This is the first report of a monitoring lure for a tortricid moth being negatively impacted by the background odor of non-host weed species present within an orchard.